Virtual Reality in Science Education: A Systematic Literature Review on Students’ Learning Motivation - Alifia Hasna Azzah Fillah; Arif Widiyatmoko; Novi Ratna Dewi; Sudarmin Sudarmin (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The growing use of Virtual Reality (VR) in science education has attracted considerable attention due to its potential to create immersive, interactive learning experiences. However, previous studies have mainly focused on cognitive outcomes, while research specifically examining students’ learning motivation remains fragmented. Therefore, this study aims to analyze publication trends, country contributions, mapping of academic fields, and the implementation of VR in science education related to students’ learning motivation. This study employed a Systematic Literature Review (SLR) approach following the PRISMA 2020 guidelines. Data were collected from the Scopus database using Publish or Perish 8, covering publications from 2016 to 2026, and 25 selected articles were analyzed qualitatively. The findings indicate that research on VR in science education has increased significantly, particularly after 2020, with the United States, Taiwan, Spain, and China as the major contributors. The studies were dominated by Computer Science and Social Sciences, reflecting the interdisciplinary nature of VR research. Furthermore, VR was found to enhance students’ learning motivation through immersive experiences, interactivity, engagement, and contextual visualization. However, excessive immersion may increase cognitive load if not supported by appropriate instructional design. Therefore, VR should be integrated with appropriate pedagogical strategies to create more engaging, student-centered science learning environments.